Q: dd these two polynomials (3x^2 + 5x + 2) + (5x^2 – 3x - 7)

A: (3x^2 + 5x + 2) + (5x^2 – 3x - 7) = 3x^2 + 5x + 2 + 5x^2 – 3x - 7 = 8x^2 + 2x - 5

twistedechoes|Points 26|

Question

Asked 9/9/2012 12:00:32 PM

Updated 7/5/2014 11:14:52 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [7/5/2014 11:12:35 AM]

Rating

3

(3x^2 + 5x + 2) + (5x^2 – 3x - 7)

= 3x^2 + 5x + 2 + 5x^2 – 3x - 7

= 8x^2 + 2x - 5

= 3x^2 + 5x + 2 + 5x^2 – 3x - 7

= 8x^2 + 2x - 5

Added 7/5/2014 11:14:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/5/2014 11:29:54 AM]

Multiply this polynomial: (6x^2y^4)(- 5x^3y) **Weegy:** 2(2x/3 + 7) - 3 = 5x 4x/3 + 14 - 3 = 5x 11 = 11x/3 x = 3 y = 2(3)/3 + 7 = 9 x(y) = 3(9) = 18. Answer is d. (More)

Question

Expert Answered

Updated 6/8/2014 4:50:02 PM

1 Answer/Comment

(6x^2y^4)(- 5x^3y) = -30x^5y^5

Added 6/8/2014 4:50:02 PM

This answer has been confirmed as correct and helpful.

Using F.O.I.L, multiply: (3x^2 + 5) (3x^2- 5) **Weegy:**
(3x^2 + 5) (3x^2- 5)
= 9x^4 + 15x^2 - 15x^2 - 25
= 9x^4 - 25
(More)

Question

Expert Answered

Updated 6/16/2014 3:00:31 PM

0 Answers/Comments

27,002,647 questions answered

There are no comments.